At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
x^2 - 3x - 4 = 0 factor it.
We first need to set it up in the form \(ax^2+bx+c=0\)
Ok I got that. I have x^2-3x-4=0 but I am not sure where to go from there.
you can use the quadratic formula or just factor it to (x+b)(x-b) form. and then solve for (x+b)=0 and (x-b) = 0 to get your solutions
We need to find 2 numbers that when you add them they equal -3 and when you multiply them they equal -4
Well that would be -4 and 1.
so, in (x+b)(x-b)=0 form it would be?
So basically then we replace -3x with -4x +1x
So our equation would look as follows \(x^2-4x+1x-4\)
(x-4)(x+1) = 0 after you put it in that form x - 4 = 0 and x + 1 = 0 solve for x to get your solutions.
Then we group the first 2 terms and teh last 2 terms \( (x^2-4x)+(x-4)=0
Then we factor out from each bracket x(x-4)+1(x-4)=0
At which point?
Well, she is asking how to find the solution, I have no idea what you are showing.. the original equation is x^2 - 3x - 4. factored out (x-4)(x+1)= 0 x = -1 x =4
x^2 - 4x + x -4 can just be simplified to x^2 -3x - 4 .....
Yes but I am just demonstrating how you factored it out This is the typical way it is taught in school and when it becomes more challenging then it is imperative that you write it out in this fashion
It looks more complicated with your method x^2 -3x -4 you know that the values are 1 and - 4. just put that like this (x-4)(x+1) = 0
I am lost after the x^2-4x+1x-4=0..Solving by factoring
Ok so after the (x-4)(x+1)=0 that gives me x how?
(x-4)(x+1)=0 you put x-4=0 and x+1=0 to get your solutions .
3x2−3x−4=0 swiss, i would use the quadratic formula. instead of trying to factor it.
You can use whtvr it makes no diff as long as you get your answer
Your method is much more complicated than it needs to be, just make it simple..
The only reason why I was showing him that method since that is the method taught in schools
Plus your method wont work for complicated equations trust me kid
Ok so x= 4, -1?
Yes, those are your solutions.
OMG THEY ACTUALLY EXCIST o-o
I have been using that face for so many times like this.........they will witness the spam of there lives when they come back XD
stalking profile now